2017
DOI: 10.1111/jmft.12229
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable Emotional Expression In Emotion Focused Couples Therapy: Relating Interactional Processes To Outcome

Abstract: This study examined whether interactions characterized by high expression of emotional vulnerability in one partner followed by a highly supportive response style by the other partner predicted greater improvement on domains of forgiveness, unfinished business, trust, and relationship satisfaction in a sample of 32 couples presenting for Emotion Focused Couples Therapy with unresolved emotional injuries. For each outcome measure, two separate hierarchical regression models were tested (injured partner vulnerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 32 publications
3
24
0
1
Order By: Relevance
“…Increases in emotional closeness served as a mechanism of change for men and women participating in behavioral and integrative couple therapy at VA hospitals (Doss et al, 2015). In a study of Emotion Focused Couple Therapy (EFCT), observed partner supportiveness in session acted as a mediator of change in satisfaction (McKinnon & Greenberg, 2017). Additionally, the occurrence of an emotional softening event during EFCT predicted gains in satisfaction during treatment (Dalgleish, Johnson, Moser, Wiebe, & Tasca, 2015).…”
Section: Mechanisms Of Change During the Interventionmentioning
confidence: 99%
“…Increases in emotional closeness served as a mechanism of change for men and women participating in behavioral and integrative couple therapy at VA hospitals (Doss et al, 2015). In a study of Emotion Focused Couple Therapy (EFCT), observed partner supportiveness in session acted as a mediator of change in satisfaction (McKinnon & Greenberg, 2017). Additionally, the occurrence of an emotional softening event during EFCT predicted gains in satisfaction during treatment (Dalgleish, Johnson, Moser, Wiebe, & Tasca, 2015).…”
Section: Mechanisms Of Change During the Interventionmentioning
confidence: 99%
“…While indirectly targeted in TBCT, both IBCT and emotionally focused couple therapy (EFCT) directly target this construct through empathic joining and fostering safe and responsive emotional connections, respectively. Observed in-session partner supportiveness (McKinnon & Greenberg, 2017) and emotional softening (Dalgleish et al, 2015) predicted improvements in relationship satisfaction in EFCT. Furthermore, similar constructs such as emotional closeness and emotional intimacy function as a mechanism in TAU couple therapy and the OR program (Doss et al, 2015; Roddy, Stamatis, et al, 2020).…”
Section: Previous Research On Mechanisms During Couple Interventionsmentioning
confidence: 99%
“…A great deal of research in EFT‐C has focused on facilitating resolution when working with couples confronting an emotional injury (e.g., Greenberg et al, 2010; Halchuk et al, 2010; Makinen & Johnson, 2006; McKinnon & Greenberg, 2013, 2017). In recent studies that have tested the key transformative elements in the resolution process, Mckinnon and Greenberg (2013, 2017) indicated that expression of vulnerability by the injured partner predicted the other partner’s responsiveness, as well as greater injury resolution and trust. However, for these salubrious effects to occur, the partners need to accurately perceive each other's vulnerability.…”
Section: Accuracy and Bias In Partners’ Perceptionmentioning
confidence: 99%